Modern Approaches in Money Laundering Cases: Analysis of a Review of German and EU Court Decisions (2025) - Litkevych , Volodymyr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
This article presents a doctrinal legal analysis of court decisions in cases concerning money laundering (ML) rendered in 2025, with due regard to § 261 of the German Criminal Code (Strafgesetzbuch, StGB) and the provisions of the German Anti-Money Laundering Act (Geldwäschegesetz, GwG). The study is based on a review of eleven selected court decisions prepared by German scholars M. El-Ghasi and J. Klotz and published in the specialized legal journal Geldwäsche & Recht [1].The court decisions are examined using a unified analytical framework that encompasses the factual background of the case, the key legal issue, the relevant normative context, the reasoning of the court, and the resulting doctrinal conclusions. On this basis, the study systematizes current doctrinal approaches reflected in the judicial practice of German and EU courts concerning the interpretation and application of criminal law and related mechanisms for combating money laundering (AML).The subject of the study is judicial practice in ML cases as understood in German legal doctrine. The analysis covers approaches developed by German and EU courts with respect to the interpretation and application of § 261 StGB, the GwG, and Directive (EU) 2015/849, in particular regarding the qualification of money laundering, the limits of criminal liability for self-laundering, procedural standards for criminal prosecution and asset confiscation, as well as the interaction between criminal law and AML mechanisms, including compliance obligations and financial supervision.The focus of the study lies in identifying and systematizing doctrinally significant legal positions emerging from judicial practice in ML cases. Court decisions are considered not as independent empirical material, but as a source of legal reasoning relevant to understanding the institutional logic of the criminalization of money laundering.In particular, the study examines the distinction between predicate offenses and autonomous money laundering offenses; the interpretation of the self-laundering exception under § 261(7) StGB and the criteria for the criminal liability of predicate offenders; procedural limits on the application of the ne bis in idem principle and the standard of initial suspicion; and the role of asset confiscation and related non-criminal instruments within the integrated AML framework.The methodological basis of the study consists of a structured analysis of court decisions using a unified scheme (factual circumstances – legal issue – normative context – judicial reasoning – doctrinal conclusion). The research employs a formal-dogmatic method to analyze criminal, criminal-procedural, and administrative AML norms; a functional-teleological method to assess the criminal-law significance and regulatory objectives of AML measures; and a systemic method to conceptualize AML as an integrated set of criminal-law, procedural, confiscation-related, and compliance instruments.The scientific value of the study lies in its doctrinal interpretation of selected representative court decisions of German and EU courts in the field of anti-money laundering, as well as in elucidating the institutional logic of ML criminalization in German and EU law based on judicial reasoning. The findings contribute to a methodologically sound understanding of foreign judicial practice, reduce the risks of its uncritical reception in national legal discourse, and deepen the doctrinal understanding of money laundering as an autonomous criminal-law phenomenon.